Kajian Sistem Pengolahan Pisang Sale dengan Menggunakan Gas Elpiji - ruddin, Naza (International Journal of Natural Science and Engineering, 2018)
Bananas sale or pisang sale  is a popular traditional food in Aceh  and its production  mostly comes from the area of northern Aceh and east Aceh. Traditional banana processing process is using fumigation method by wood fuel and coconut shell. Traditional banana sale is dark brown and tastes is less good. The banana processing process here uses a heating cabinet with a heating method and with an average temperature of 90-70 ° C for 14 hours. The purpose of the study was to obtain the optimal temperature used in the processing of banana sale in order to know the quality and good quality of on the traditional way. The preheating process with high temperature is to accelerate the decrease in water content in bananas so that the drying process becomes faster. The quality of banana sale is produced with a reddish color and very sweet because of glucose in the banana. The cooking process is by using LPG gas. The benefits of using LPG gas are because it is environmentally friendly, does not cause air pollution and the result of LPG combustion does not leave the smell, so it is suitable for use as fuel or raw materials for industry